2021
DOI: 10.1177/00469580211056389
|View full text |Cite
|
Sign up to set email alerts
|

Mental State of Students During the Pandemic and Affecting Factors: A Cross-Sectional Study

Abstract: Evaluation of the psychological symptoms in healthcare students and the development of new strategies to improve their mental health are of great importance. The study was aimed at determining the mental state of students, prospective healthcare workers, during the pandemic, and the influencing factors. The descriptive cross-sectional study was conducted at a Manisa Celal Bayar University Faculty of Health in Turkey. The sociodemographic characteristics questionnaire, Fear of COVID-19 Scale, and Brief Symptom … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 25 publications
1
4
0
Order By: Relevance
“…In this study, the total score of the FCV-19S was 19.20 (± 6.81) out of a possible 35, indicating mild fear of COVID-19 during the pandemic. These findings were similar to other nursing student studies such as: Turkey (19.35 ± 5.90) (Nehir & Gungor Tavsanli 2021 ), Egypt among first year nursing students (17.96 ± 5.10) (Metwally Elsayed & Ahmed Ghazi 2021 ) and South Africa among fourth year students (20.27 ± 7) (Chipps et al 2022 ). The total FCV-19S score reported in this study may be because of the orientation programme offered by the university that included support from academic and clinical staff together with information of COVID-19, which reduced their feelings of anxiety (Chipps, Jarvis & Brysiewicz 2021 , Jarvis et al 2021 ).…”
Section: Discussionsupporting
confidence: 89%
“…In this study, the total score of the FCV-19S was 19.20 (± 6.81) out of a possible 35, indicating mild fear of COVID-19 during the pandemic. These findings were similar to other nursing student studies such as: Turkey (19.35 ± 5.90) (Nehir & Gungor Tavsanli 2021 ), Egypt among first year nursing students (17.96 ± 5.10) (Metwally Elsayed & Ahmed Ghazi 2021 ) and South Africa among fourth year students (20.27 ± 7) (Chipps et al 2022 ). The total FCV-19S score reported in this study may be because of the orientation programme offered by the university that included support from academic and clinical staff together with information of COVID-19, which reduced their feelings of anxiety (Chipps, Jarvis & Brysiewicz 2021 , Jarvis et al 2021 ).…”
Section: Discussionsupporting
confidence: 89%
“…In another study of 2605 Norwegian undergraduate nursing students, the FCV-19S item mean score was 2.45 (SD ± 0.8) [ 46 ]. Another study evaluated the psychological states of 828 healthcare students in Turkey and found a lower mean FCV19S score of 19.35 (SD ± 5.90) [ 19 ]. Our participants’ higher score for the FCV-19S might be due to the perceived risk of the highly contagious Corona, along with local social media news of the upsurge in infected cases and continued overcrowding in hospital admissions [ 47 ].…”
Section: Discussionmentioning
confidence: 99%
“…A meta-analysis reviewed 27 studies assessing the psychological effects of COVID-19 among 90,879 college students in 15 countries, and found that 39.4%, 31.2%, 26.0%, 29.8%, and 50.5% of students had anxiety, depression, stress, post-traumatic stress, and impaired sleep quality, respectively [ 18 ]. The study reported the adverse psychological effects on university or college students, and highlighted the necessity of establishing appropriate health interventions or strategies to meet their emotional and psychosocial needs [ 19 , 20 , 21 ]. Nehir and Gungor Tavsanli (2021) found a significant relationship between the fear of COVID-19 and students’ emotional states.…”
Section: Background Literaturementioning
confidence: 99%
See 2 more Smart Citations